Web-Based Knowledge Management System Application to Improve Employee Activities - Dody Dody; Nasril Sany; Pritasari Palupiningsih; Firmansyah Apryadhi (JURNAL SISFOTEK GLOBAL, 2023)
The need for information is very high in the current 4.0 era, every organization needs fast, accurate and detailed information. Currently there is documentation at the Indonesian Medical Council Secretariat regarding knowledge on how to handle employee problems which can help the employee's own performance so that it has an impact on secretariat activities that feel ineffective. Based on the results of the analysis that has been carried out, there is a lot of important knowledge at the Indonesian Medical Council Secretariat whose function is to support activities in Health Institutions. The methodology used in this research is to use Beccera Fernandez which was developed by Beccera and Sabherwal. The data collection methods used were observation, interviews, literature study, while the Knowledge Management System implementation used the Knowledge Management Process, and the KMS design used the Unified Modeling Language (UML) modeling. The programming languages used in building the system are PHP and MySQL. The concept of knowledge sharing among employees was applied as a result of a study conducted at the Indonesian Medical Council Secretariat. This is implemented on the website so that individual employee knowledge is not simply lost.